Détective et Police Magazine à l’heure américaine (1931) - Laetitia Gonon (Criminocorpus)
This article will show how two french weekly magazines, Détective and Police Magazine, report american crimes in their pages, in the early 1930s. Crime journalists take indeed a double stand with the american information: proximity and distance. They show themselves close to the information, emphasizing privileged sources, local correspondents and police officers, or highlighting in their articles english words, translated quotes. Simultaneously, reporters adapt the information, draw parallels between american and french civilizations in order to get the readers’ attention, and, in doing so, differentiate themselves from the american world, because it is considered more extreme, more violent. Finally, Détective distance itself from the fascination with american crime stories.